Summer pruning of sweet cherry trees and an inquiry of winter frost damages - Vaszily, B.; Gonda, I.; Soltész, M. (International Journal of Horticultural Science, 2011)
One of the most demanded research projects is the intensification of fruit production. The use of dwarfing stocks is a moderate solution as their effect is scarcely satisfactory. Climatic conditions of Hungary are continental in Eastern Europe, where Atlantic and Mediterranean effects are interacting with the continentals in a kind of basin with characters of its own. Capricious meteorological episodes are often disturbing the security of development and fruiting of trees:• winter frosts are damaging the cambium and fruiting structures of trees• late spring frosts destroy cambium and flowers• early autumn frosts hurt the leaves• excessive precipitation impairs the growing fruits• drought periods during the summer caused water stress disturbing water husbandry.Vigorous stocks still prevail in the practice, and they ought to withstand challenges of weather hazards. The strong vigour of plants delaysthe process of senescence and the tendency of getting bald, and regeneration of plants is a sign of vitality. In present research, the trees have been trained on vigorous Prunus mahaleb stocks. Summer pruning was one of the important tools of intensive growing techniques. They were compared with traditional techniques and with plastic foil protected trees observing the vegetative as well as generative growth of them.